Assessing the potential of enhanced primary clarification to manage fats, oils and grease (FOG) at wastewater treatment works - Collin, Thomas Denis; Cunningham, Rachel; Asghar, Mohammed Qasim; Villa, Raffaella; MacAdam, Jitka; Jefferson, Bruce (Elsevier, 2020)
Daily, sewage treatment works (STWs) receive large volumes of fats, oils and greases (FOG), by-products of food preparation. To increase FOG removal at STW, conventional primary sedimentation tanks (PSTs) can be enhanced using chemical coagulant or through dissolved air flotation (DAF) techniques. This work aimed to assess the potential benefits of enhanced primary treatment for FOG removal through an energy and costs analysis. To achieve this, a five-year sampling programme was conducted monthly at 15 STWs measuring FOG concentrations in crude and settled sewage (i.e. after primary treatment). In addition, two DAF pilot systems were trialled for four months and their performance, in terms of FOG removal, was assessed and compared to that of a control primary clarifier. Across the 15 STWs, influent FOG concentrations were found at 57 ± 11 mg.L−1. Chemical coagulants dosed prior to PSTs increased FOG removal rates on average to 71% whilst traditional sedimentation only achieved 50% removal. Effluent FOG concentrations were found between 12–22 mg.L−1 and 19–36 mg.L−1 respectively. By contrast, DAF achieved FOG effluent concentrations on average at 10 ± 4 mg.L−1 corresponding to 74% removal from a relatively low influent concentration of 40 ± 30 mg.L−1. Thus, enhanced primary treatments have the potential to reduce organic load to secondary treatment and increase energy generation through anaerobic digestion. The overall net energy balance was estimated at 2269 MWh.year−1 for the DAF compared to 3445 MWh.year−1 for the chemically-enhanced PST making it a less financially attractive alternative. Yet, in the case where the works require upgrading to accommodate flow or load increases, DAF appeared as a sensible option over sedimentation offering significantly lower capital costs and footprint. In relation to FOG management, upgrading all STWs is not realistic and will require understanding where the benefits would be the highest.
Keywords: Dissolved air flotation (DAF); Sewage treatment works (STWs); )Hexane extractable material (HEM); Primary sedimentation tanks (PSTs)